Voices of Alzheimer Caregivers on Positive Aspects of Caregiving - Cheng, Sheung-Tak; Mak, Emily P M; Lau, Rosanna W L; Ng, Natalie S S; Lam, Linda C W (The Gerontologist, 2016)
To discover positive gains as constructed by family caregivers of relatives with Alzheimer's disease. Fifty-seven Hong Kong Chinese primary caregivers provided 669 diary recordings over an 8-week period, describing daily events and experiences in which positive gains were achieved. The diaries were analyzed independently by two researchers using thematic analysis. Ten themes related to positive gains were identified: (a) insights about dementia and acceptance of the condition, (b) a sense of purpose and commitment to the caregiving role, (c) feelings of gratification when the care-recipient (CR) was functioning relatively well, (d) mastering skills to handle the CR, (e) increased patience and tolerance, (f) cultivating positive meanings and humor amidst difficult circumstances, (g) letting go of things, such as when the CR's qualities had been lost or personal agenda had become unrealistic, (h) developing a closer relationship with the CR, (i) finding support, and (j) feeling useful helping other caregivers. In addition to treating negative outcomes such as depression, practitioners and researchers should, identify means to promote positive gains. Strategies mentioned in the caregivers' diaries, such as reframing stressful situations in a more positive light, may provide input into the design of such interventions.